(untitled) (Biological Sciences - PJSIR, 2001)
Studies on autolysis of proteolytic enzyme like cathepsin revealed that the purified enzyme was autolysed by metastasisorduetoabsenceofstabilizer.CrudetissuewasextractedwithsodiumchloridebuffercontainingEDTAand Triton x-I00.Extract was analyzedfortotal proteinandproteaseactivity.Protein/peptide was analyzed/purified using SDS polyacrylamide gelelectrophoresis, ionexchange chromatography and reversed phase HPLC. Results indicated the autolysis during purification of enzyme. It is concluded that during and after purification suitable stabilizer of enzyme should be added. In vitro experiment indicated that in vivo (cancerous tissue), the imbalance of specific stabilizer/inhibitors of proteasecause autolysisof enzyme and theresulting peptides cause the damaging effects.